“But Saul Held His Peace”: Sebuah Analisis Leksikal-Sintaktis 1 Samuel 10:27 - Steven (Verbum Christi: Jurnal Teologi Reformed Injili, 2024)
A problem raised in the text of 1 Samuel 10:27, since the word כמחריש in Masoretic Text is conspicous both in terms of the text transmission as well as in the level of exegesis. In the context of the narrative, after appointing Saul as the first king of Israel, some of the people seem to question Saul’s credibility. This leads to harsh comment on the new king. Interestingly, some interpretations seem to portray a kind of Saul’s response to the comment in 1 Samuel 10:27, while others completely silence. This article will come with a suggestion to the passage by imploring textual criticism, deciding the possibly fitting word for כמחריש, considering its larger narrative context, and then doing lexical-syntactical analysis to the passage. This article contends that the correction made by the LXX that supported by the DSS and Josephus’ writing is closer to the original.